Experimental investigation of L- and H-mode detachment via the divertor Thomson scattering at ASDEX Upgrade. (1st June 2022) - Cavedon, M.; Kurzan, B.; Bernert, M.; Brida, D.; Dux, R.; Griener, M.; Henderson, S.; Huett, E.; Nishizawa, T.; Lunt, T.; Pan, O.; Stroth, U.; et al.
Abstract: The capabilities of the newly installed divertor Thomson Scattering (DTS) diagnostic (Kurzan et al 2021 J. Inst. 16 C09012) at ASDEX Upgrade (AUG) have been demonstrated by measuring 2D electron densities n e and temperatures T e from attached to fully detached divertor conditions in L- and H-mode. The collected dataset is a breakthrough for divertor studies at AUG in which such measurements have been so far missing. Besides highlighting the strengths and limits of the DTS system, this work provides confirmations and new insights into detachment physics. The transition between partial and pronounced detachment correlates with a 2D redistribution of the electron density from the inner to the outer divertor in both L- and H-mode. In pronounced detachment, a strong parallel pressure gradient could be confirmed throughout the complete SOL. Finally, measurements of n e and T e of a stable X-point radiator revealed local temperatures as low as 1 eV within the confined plasma, whereas the pressure is shown to be constant on closed field lines.